Nudging cooperation - Kai Barron; Tuomas Nurminen (Wissenschaftszentrum Berlin für Sozialforschung (WZB), 2018)
This paper experimentally studies two simple interventions aimed at increasing public goods provision in settings in which accurate feedback about contributions is not available. The first intervention aims to exploit lying aversion by requiring subjects to send a non-verifiable ex post announcement about their contribution. The second intervention aims to nudge participants to higher contribution levels by simply labeling contributions of 16 or above as being `good'. We find that the ex post announcement mechanism does not have a significant effect on the cooperation rate. However, the nudge leads to a striking increase in the cooperation rate. We provide suggestive evidence that the nudge we use provides subjects with a focal point, helping conditional cooperators to coordinate their contributions. Moreover, despite the lack of monetary incentives to lie, we find that a non-negligible group of subjects inflate their anonymous announcements.
More recent version: http://hdl.handle.net/10419/216878
Keywords: C91; C72; H41; Z13; 330; cooperation; nudge; public good; experiment; lying; focal point